Internalization of Education Character Based on the Five Souls of Modern Islamic Boarding School Al-Ihsan Baleendah - Hasbiyallah Hasbiyallah; Mahli Nurul Ihsan (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2021)
The purpose of this article was to analyze the internalization of five soul-based education character in modern Islamic boarding schools Al-Ihsan Baleendah Bandung. This research method used qualitative research and collecting data used interview, observation and documentation techniques to reveal the concept of internalizing character values based on the five souls in the modern Islamic boarding school Al-Ihsan Baleendah. The results of this study showed that the modern Islamic boarding school education Al-Ihsan Baleendah was an Islamic educational institution that contains character values based on the five souls that were implicit in the Islamic boarding school program. The values of education character based on the five souls applied in modern Islamic boarding school involve: the soul of sincerity, the spirit of simplicity, the spirit of independence, the spirit of freedom and the spirit of ukhuwah Islamiyah. Character education based on the five souls is internalized through the example of the kyai, the habit of worshiping, the discipline of obeying the rules of the Islamic boarding school, the awareness and responsibility of the Islamic student in carrying out activities in modern Islamic boarding school Keywords: Education Character, Internalization Education Character, Islamic Boarding Scho